to be or not to be: forecast of Covid-19 epidemic development in Russia - D. M. Danilenko; A. B. Komissarov; M. A. Stukova; D. A. Lioznov (Журнал инфектологии, 2020)
Currently, the intensity of COVID-19 epidemic in Russia is declining. Most of the country’s regions are at the first stage of lifting restrictions; some regions have moved to the second and third phases. At the same time, the development of the COVID-19 pandemic in Southern hemisphere indicates the continuous circulation of SARS-CoV-2 in the world. The article provides statements arguing for the development of the «second wave» of the COVID-19 epidemic in Russia, as well as practical recommendations aimed at preparing for the autumn-winter epidemic season 2020–2021.